Quantitative Evaluation of Tactile Foraging Behavior in Pekin and Muscovy Ducks - West, Aaron K.; Xu, Emily M.; Nelson, Mitchell D.; Hart, Thomas R.; Stricker, Emelia M.; Cones, Alexandra G.; Martin, Grace M.; Strickland, Kourtney; Lambert, Devin L.; Burman, Lainey; Zhu, Bailey H.; Schneider, Eve R. (Frontiers in Physiology, 2022)
Ducks have developed a variety of foraging strategies that utilize touch sensitive bills to match their ecological niche within wetlands. These techniques include diving, sieving, dabbling, and grazing. Ducks exhibiting tactile specialization in foraging have been shown to outperform visual and non-tactile foraging ducks in behavioral experiments and have a higher percentage of light-touch mechanoreceptor neurons expressing Piezo2 in the trigeminal ganglia. Belonging to two different tribes of Anseriformes, the well-studied tactile specialist Pekin (Tribe Anatini: Anas platyrhynchos domestica) and lesser studied Muscovy (Tribe Cairinini: Cairina moschata domestica) ducks were tested on a series of experiments to assess these birds’ functional tactile acuity. Both species of duck were able to separate out and consume edible items from increasing amounts of inedible plastiline clay distractors. They could also both be trained to associate a food reward with plastiline stimuli of differing size and shape using touch alone. However, only hens of each species could learn to associate food reward with otherwise identical stimuli differing only in hardness. Pekin hens performed significantly better than Muscovy hens suggesting the anatomical specializations present in many Anatini may contribute to this type of tactile acuity. These findings have potential relevance understanding the evolution of tactile ability and waterfowl conservation.